Relating Pore‐Scale Observations to Continuum‐Scale Models: Impact of Ganglion Dynamics on Flow Transport Kinetics - Rumbidzai A. E. Nhunduru; Amir Jahanbakhsh; Omid Shahrokhi; Krystian L. Wlodarczyk; Susana Garcia; M. Mercedes Maroto‐Valer (Water Resources Research)
Abstract Continuum‐scale models used to model and predict two‐phase flow in the subsurface are often based on averaged flow parameters and do not consider pore‐scale fluid flow phenomena, for example, ganglion dynamics and thin‐film flow. As such, a major challenge in upscaling two‐phase flow for groundwater engineering applications is understanding the impact of disconnected flow and ganglion dynamics on continuum‐scale flow functions such as relative permeability‐saturation and capillary pressure‐saturation curves. In this study, we explored how changes in wettability and fluid velocity affect ganglion dynamics. We conducted pore‐scale numerical simulations with OpenFOAM to investigate the displacement of decane by water. Additionally, we examined how displaced phase saturation (a continuum‐scale flow function) responds to changes in dynamic fluid connectivity. We identified three different fluid flow regimes, that is, the connected pathway flow regime, ganglion dynamics (GD) flow regime, and droplet traffic flow regime, and studied the effects of changes in the wettability of the porous medium and the velocity of the invading fluid on the transitions between these different regimes. Our research showed that transitions between connected and disconnected pore‐scale flow regimes, which are induced by changes in fluid velocity and wettability, have a significant impact on both fluid displacement efficiency and average fluid flow transport kinetics.